(untitled) (Global Journal of Management and Business Research, 2022)
The twenty first century has seen the emergence of a global marketplace, where one can travel from country to country, across oceans, and find the same retail establishments. While this may be comforting to travelers and intriguing for locals, there are instances where global retailing has destroyed or eroded the local colour and culture. This paper outlines this cultural erosion and raises questions about the change foreign owners bring to a country and the impact on local culture and customs.